RANCANG BANGUN APLIKASI PENJUALAN ONDERDIL MOTOR DI BENGKEL CALVIN JAYA MOTOR PENGASINAN SAWANGAN - Dimas Rahmadian Prasetyo; Marhaeni Marhaeni (PROGRAM STUDI SISTEM INFORMASI INSTITUT SAINS DAN TEKNOLOGI NASIONAL (ISTN), 2022)
Calvin Jaya Motor is a place for service as well as buying and selling motorcycle parts which is quite famous for its goods that are always available, but Calvin Jaya Motor only serves offline, ie buyers come directly to the place then see and buy goods face to face, this will have Some of the shortcomings include the queuing process and it allows prospective buyers not to buy because of the crowded queues, besides that sometimes there is a human error in the daily sales recorder,this study uses data collection methods used to collect the data needed in this study, namely the method of observation, interviews and literature study, and using spiral model as development method. Keywords: Information System, Spare parts, Spiral Model